PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI MODEL ROLE PLAYING BERBANTUAN MEDIA AUDIOVISUAL - ida riana valentina, sri hartati (Phenomenon : Jurnal Pendidikan MIPA, 2015)
The purpose of this research is to improve the skills of teachers, activities, and student learning outcomes.The research design is a classroom action research consists of four phases: planning, action, observation, and reflection is done in three cycles. The subjects were 42 students in grade IVA SDN Tambakaji 04 Semarang. The techniques of data collection is using tests and non-test. Analysis using quantitative descriptive analysis and qualitative descriptive analysis. The results showed the average teacher skills first cycle was 26 including good category, increased in the second cycle to 28, and increased again in the third cycle the 34 scores obtained with very good category. The average student activity first cycle is 23.8 with enough categories, increased in the second cycle to obtain a score of 28 including both categories, and increased again in the third cycle to 34 with a very good category. Likewise, the percentage of student learning outcomes first cycle of 60%, with the lowest value and the highest 40 100, increased in the second cycle of 76%, with the lowest value and highest value 60 100, and rose again the third cycle to 86% with the lowest value of 60 , and the highest value of 100. Conclusion Research is through role playing with a model of audiovisual media, can improve the quality of science teaching include teachers skills, students activities and student learning outcomes.